Soybean-Genistein as Endocrine Disruptor on Estrous Cyclicity and Ovarian Follicular Development in Albino Rats (Rattus norvegicus) - Geraldine C. Sanchez; Ronaldo D. Dizon; Aris F. Miclat; Maria Fe S. Bulao; Julia A. Eggert (Philippine Association of Institutions for Research, Inc., 2013)
Endocrine disruptors are chemicals that interfere with the body's endocrine system and produce adverse developmental, reproductive, neurological, and immune effects in both humans and wildlife. One example of endocrine disruptor is phytoestrogen which is a group of naturally occurring compounds that have been reported to cause fertility problems in animals. The major phytoestrogen in soy products is genistein, which has potent estrogenic activity both in vitro and in vivo. Previous findings have demonstrated that the control of primordial follicle development and subsequent folliculogenesis appears to be mediated by local production and action of specific paracrine factors. Preliminary studies also have shown that steroid hormones like estrogen play a critical role in the onset of primordial follicle assembly. These findings led us to further look into the effects of genistein on estrous cyclicity and ovarian folliculogenesis specifically on pre-antral and antral follicular development including their possible effects on ovarian morphometry of sexually matured female albino rats. The objectives of the study was to determine the effects of genistein on estrous cyclicity and ovarian folliculogenesis specifically on pre-antral and antral follicular development including their possible effects on ovarian and uterine morphometry of sexually matured female albino rats. Furthermore, the study elucidated its effect on the apoptosis of granulose and theca cells resulting to follicular atresia. A total of 24 female albino rats approximately 2-3 months of age of almost the same size were used in this study.